Cross-Reactivity and Anti-viral Function of Dengue Capsid and NS3-Specific Memory T Cells Toward Zika Virus - Lim, Mei Qiu; Kumaran, Emmanuelle A. P.; Tan, Hwee Cheng; Lye, David C.; Leo, Yee Sin; Ooi, Eng Eong; MacAry, Paul A.; Bertoletti, Antonio; Rivino, Laura (Frontiers in Immunology, 2018)
ZZika virus (ZIKV), a flavivirus with homology to dengue virus (DENV), is spreading to areas of DENV hyper-endemicity. Heterologous T cell immunity, whereby virus-specific memory T cells are activated by variant peptides derived from a different virus, can lead to enhanced viral clearance or diminished protective immunity and altered immunopathology. In mice, CD8+ T cells specific for DENV provide in vivo protective efficacy against subsequent ZIKV infection. In humans, contrasting studies report complete absence or varying degrees of DENV/ZIKV T cell cross-reactivity. Moreover, the impact of cross-reactive T cell recognition on the anti-viral capacity of T cells remains unclear. Here we demonstrate that DENV-specific memory T cells display robust cross-reactive recognition of ZIKV NS3 ex vivo and after in vitro expansion in respectively n=7/10 and n=9/9 dengue-immune individuals tested. In contrast, cross-reactivity towards ZIKV capsid is low or absent. Cross-reactive recognition of DENV or ZIKV NS3 peptides elicits similar production of the anti-viral effector mediators IFN-γ, TNF-α and CD107a. We identify 9 DENV/ZIKV cross-reactive epitopes, 7 of which are CD4+ and 2 are CD8+ T cell epitopes. We also show that cross-reactive CD4+ and CD8+ T cells targeting novel NS3 epitopes display anti-viral effector potential towards ZIKV-infected cells, with CD8+ T cells mediating direct lyses of these cells. Our results demonstrate that DENV NS3-specific memory T cells display anti-viral effector capacity towards ZIKV and point towards a potential beneficial effect in humans of pre-existing T cell immunity to DENV upon ZIKV infection.